Involvement of the P2X7 Purinergic Receptor in Colonic Motor Dysfunction Associated with Bowel Inflammation in Rats - Antonioli, Luca; Giron, Maria Cecilia; Colucci, Rocchina; Pellegrini, Carolina; Sacco, Deborah; Caputi, Valentina; Orso, Genny; Tuccori, Marco; Scarpignato, Carmelo; Blandizzi, Corrado; Fornai, Matteo (PLOS ONE, 2015)
Background and Purpose Recent evidence indicates an involvement of P2X7 purinergic receptor (P2X7R) in the fine tuning of immune functions, as well as in driving enteric neuron apoptosis under intestinal inflammation. However, the participation of this receptor in the regulation of enteric neuromuscular functions remains undetermined. This study was aimed at investigating the role of P2X7Rs in the control of colonic motility in experimental colitis. Experimental Approach Colitis was induced in rats by 2,4-dinitrobenzenesulfonic acid. P2X7R distribution was examined by immunofluorescence analysis. The effects of A804598 (selective P2X7R antagonist) and BzATP (P2X7R agonist) were tested on contractions of longitudinal smooth muscle evoked by electrical stimulation or by carbachol in the presence of tetrodotoxin. Key Results P2X7Rs were predominantly located in myenteric neurons, but, in the presence of colitis, their expression increased in the neuromuscular layer. In normal preparations, A804598 elicited a negligible increase in electrically induced contractions, while a significant enhancement was recorded in inflamed tissues. In the presence of Nω-propyl-L-arginine (NPA, neuronal nitric oxide synthase inhibitor) the A804598 effects were lost. P2X7R stimulation with BzATP did not significantly affect electrical-induced contractions in normal colon, while a marked reduction was recorded under inflammation. The inhibitory effect of BzATP was antagonized by A804598, and it was also markedly blunted by NPA. Both P2X7R ligands did not affect carbachol-induced contractions. Conclusions and Implications The purinergic system contributes to functional neuromuscular changes associated with bowel inflammation via P2X7Rs, which modulate the activity of excitatory cholinergic nerves through a facilitatory control on inhibitory nitrergic pathways.